The role of inflammation in subventricular zone cancer - Bardella, C; Al-Shammari, A; Soares, L; Tomlinson, I; O'Neill, E; Szele, F (Elsevier, 2018)
The adult subventricular zone (SVZ) stem cell niche has proven vital for discovering neurodevelopmental mechanisms and holds great potential in medicine for neurodegenerative diseases. Yet the SVZ holds a dark side - it can become tumorigenic. Glioblastomas can arise from the SVZ via cancer stem cells (CSCs). Glioblastoma and other brain cancers often have dismal prognoses since they are resistant to treatment. In this review we argue that the SVZ is susceptible to cancer because it contains stem cells, migratory progenitors and unusual inflammation. Theoretically, SVZ stem cells can convert to CSCs more readily than can postmitotic neural cells. Additionally, the robust long-distance migration of SVZ progenitors can be subverted upon tumorigenesis to an infiltrative phenotype. There is evidence that the SVZ, even in health, exhibits chronic low-grade cellular and molecular inflammation. Its inflammatory response to brain injuries and disease differs from that of other brain regions. We hypothesize that the SVZ inflammatory environment can predispose cells to novel mutations and exacerbate cancer phenotypes. This can be studied in animal models in which human mutations related to cancer are knocked into the SVZ to induce tumorigenesis and the CSC immune interactions that precede full-blown cancer. Importantly inflammation can be pharmacologically modulated providing an avenue to brain cancer management and treatment. The SVZ is accessible by virtue of its location surrounding the lateral ventricles and CSCs in the SVZ can be targeted with a variety of pharmacotherapies. Thus, the SVZ can yield aggressive tumors but can be targeted via several strategies.